Performance of Medium Duration Rice Cultivars on Growth, Productivity and Profitability under South Andaman Condition of India - Bommayasamy, N.; Ramakrishna, Y.; Kapoor, Pooja (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was carried out during both July to November 2019 and 2020 on the farmers’ fields in the Guptapara village of South Andaman, India, to determine the growth and yield performance of a medium-duration rice cultivar and its suitability. The treatments included five medium-duration rice cultivars consist of Jaya, ADT 45, CARI dhan 3, CARI dhan–6, and CARI dhan-7 laid out in Randomised Complete Block Design with four replications. The results showed that medium-duration rice cultivars exhibited significant variations in growth and yield attributing characteristics, such as leaf area index, root length, root dry weight, the number of productive tillers m-2, panicle length, filled grains panicle-1, and test weight. The growth attributes of rice were significantly influenced by medium-duration rice cultivars, except plant height. Regardless of the duration of the rice cultivars, CARI dhan 7 exhibited significantly greater root length and dry weight, measuring 33.2 cm and 6.37 g hill-1, respectively. CARI dhan 7 had substantially higher productive tillers (357 m-2), filled grains panicle-1 (121.6), grain (4790 kg ha-1), and straw yield (7390 kg ha-1), which was statistically comparable to CARI dhan-6. CARI dhan 7 had the highest gross return of ` 71595 ha-1, a net return of ` 36946 ha-1, and a benefit-cost ratio of 2.07. The medium-duration rice cultivar CARI dhan 7 performed better and more suitable in low-lying areas of South Andaman.